Investigating Iraqi EFL College Students’ Multiple Intelligences (Journal of the College of Education for Women, 2019)
Various theories on learning have been developed with increasing frequency in the lastfew decades. In tandem with this, Multiple Intelligence theory appeared as a new approach toeducation as well as an important theory in the field of language learning. Gardner explainsthat all human beings have different intelligence fields and a potential to develop them. Theseintelligences are (verbal-linguistic, logical-mathematical, visual-spatial, musical, bodilykinesthetic,interpersonal, intrapersonal, naturalistic, and Existential).This study aims at investigating Multiple Intelligences of Iraqi college EFL students. Toachieve the aims of the study, a questionnaire is adopted according to Birmingham modelwhich includes 40 items with a five point scale (this is not like me at all, this is a bit like me,this is sometimes like me, I am like this more often than not, I am always like this), andcovers all types of Multiple Intelligence theory. The sample of the present study consists ofthe first and second year female students from Department of English Language, College ofEducation for Women/ University of Baghdad.After ensuring the validity and reliability of the questionnaire, the researchers have appliedthe questionnaire on 18th of May 2014. The results show that most of the Iraqi collegestudents prefer music with learning, as well as, musical, intrapersonal and interpersonalintelligences as they most frequently used and accepted. Finally, conclusions,recommendations and suggestions for future work are put forward.Key Terms: Multiple Intelligences Theory, Learning.